Understanding the multi-dimensional nature of poverty - Goel, Richa (Emerald studies in sustainable approaches to poverty alleviation series, 2025)
The authors of this edited collection take a holistic approach to poverty, recognizing interconnected factors on a global scale. This timely collection aids in developing more effective strategies for combating poverty and fostering a fairer, more prosperous future